E-Report Online Berbasis SMS Gateway (Studi Kasus SMA Negeri 1 Lebakwangi) - Jajang Zaini Rois; Toni Khalimi; Yusuf Ginanjar (NUANSA INFORMATIKA, 2010)
Media information is one important factor to support the development of education. The rapid development of technology allows more easily the delivery of information. Utilization of media progress information deemed necessary to support the delivery of information to the users information and routine activities is increasing. Each student has the aptitude and capability of each that can be measured based on the input and output of the process being operated at the school. Abilities and behaviors which measures the success of a student. Output generated by the capabilities and behavior of students in private schools is a globally knowledgeable and insightful, useful for the community, have a strong personality and in addition it also produces a report in the form of education for the record book report student learning outcomes in schools. Education Reports book useful as a medium of information about the results and progress of students in the school for parents. Often times due to various things, information about the student learning outcomes are not delivered properly to the parents. This causes the control and motivation of parents to be reduced to the students. Therefore, the necessary devices to help information delivered supporting the education of students report that one of them is by utilizing advances in information technology. By utilizing information technology-based mobile (SMS Gateway), are expected to help information delivered education of high school students report to parents each and can be tightened control and activate the role of parents of students who are more or less affect the progress and development of students.Keywords : SMS Gateway, E-Report